2020
DOI: 10.3390/su12166647
|View full text |Cite
|
Sign up to set email alerts
|

Gasification of RDF and Its Components with Tire Pyrolysis Char as Tar-Cracking Catalyst

Abstract: The composition of gas produced by the gasification of refuse-derived fuel (RDF) can be affected by the content of individual components of RDF and their mutual interactions. In this work, plastics, paper, wood, textile and RDF were gasified in a two-stage gasification system and the obtained tar yields and product gas quality were compared. The two-stage reactor consisted of an air-blown gasifier and a catalytic reactor filled with carbonized tire pyrolysis char as the tar-cracking catalyst. Tire pyrolysis ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…While high temperatures lead to thermal cracking of tars, low temperatures have previously been observed to cause repolymerization and oxygenation of hydrocarbon compounds, increasing the tar content of the product gas. Similarly, the increase in tar content after the condenser can be attributed to the formation of oxygenated compounds [45] . The following GC-MS analysis was performed to investigate relative percentages of tar components.…”
Section: Resultsmentioning
confidence: 99%
“…While high temperatures lead to thermal cracking of tars, low temperatures have previously been observed to cause repolymerization and oxygenation of hydrocarbon compounds, increasing the tar content of the product gas. Similarly, the increase in tar content after the condenser can be attributed to the formation of oxygenated compounds [45] . The following GC-MS analysis was performed to investigate relative percentages of tar components.…”
Section: Resultsmentioning
confidence: 99%
“…Tire char activated at a temperature of 900 °C and with the highest specific surface area (46.5 m 2 g −1 ) exhibited the highest toluene conversion with 92% compared to char with a surface area of 43.4 m 2 g −1 , which achieved a conversion of 89%. Suhaj et al [32] studied the use of tire pyrolysis char as a tar cracking catalyst during the gasification of refuse derived fuel, and the results showed that using the catalyst resulted in an increase in H 2 concentration due to the reduction of tar. Char catalytic activity can be enhanced by impregnation with metals.…”
Section: Introductionmentioning
confidence: 99%
“…This journal is © The Royal Society of Chemistry 2023 Sustainable Energy Fuels, 2023, 7, 3505-3540 | 3523 the formation of tar during biomass gasication, 153 leading to improved H 2 and H 2 /CO yields. 154,155 Solving the tar problem during biomass gasication would lead to enhanced biomass conversion to gas and improved syngas quality. As already discussed in Section 2, signicant tar reduction can already be achieved through innovative gasier designs and operations.…”
Section: Primary Catalysts Have Been Effective In Limiting and Contro...mentioning
confidence: 99%